Hidden in Plain Sight: "Haratine" in Nouakchott's "Niche-Settlements" - McDougall, E. Ann (The International journal of African historical studies, 2015)
[...]they were seen as different and treated differently from "other" freed slaves. [...]there is an inference of "stasis" rather than change attached to Baba Ahmed's interpretation that raises questions in light of this study.